Review: Adrian Holliday (2007). Doing and Writing Qualitative Research - Thakur, Manish K. (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2008)
The book fruitfully combines discussions on qualitative research methods with the craft of academic writing. While detailing different stages involved in qualitative research, it accords appreciable attention to the fundamental epistemological premises of different qualitative research genres. Yet, its central concern is to demonstrate ways and means to manage researcher’s subjectivity in the writing of qualitative research. The book looks at the act of writing as crucial to the twin concerns of rigor and validity in qualitative research. It privileges writing as an important methodological resource that qualitative researchers employ to make the workings of their research procedures transparent and establish their accountability in relation to specificities of a given research setting. Given this focus, the eight chapters of the book discuss at length issues such as authorial voice, the trials and tribulations of transition from data to written study, the reflexivity of the researcher as writer, and the demanding expectations of cautious detachment in reporting the people, setting, and the worlds and sensitivities that are part of any qualitative research enterprise. URN: urn:nbn:de:0114-fqs090198